Design und künstliche Intelligenz : Theoretische und praktische Grundlagen der Gestaltung mit maschinell lernenden Systemen - Engenhart, Marc (Birkhäuser, 2022)
Designing with intelligent applications Intelligent machines are no longer merely the stuff of science fiction; we are already surrounded by a multitude of intelligent applications. For example, the information feeds of large social media platforms are compiled and designed for individual users by means of algorithms. This often-unnoticed process in design practice contrasts conspicuously with a glaring gap in terms of the design-centered practice of application-oriented, AI-based design. This book shows how designers' tasks, roles, and understanding expand when machines take on design decisions and when the concept and practice of what we call creativity fundamentally shifts. Thus, this book adds to our knowledge of how designers can apply machine learning productively. Relevant models and current applications of artificial intelligence in design Principles of good and ethical practice in designing with machine learning Seven discipline-specific case studies plus a chapter on practical applications